Development and characterization of low metallic friction composites filled with brass chips. (3rd July 2022) - Yusubov, F. F.
ABSTRACT: This research is focused on investigating new low metallic non-asbestos organic friction composite materials obtained by conventional powder metallurgy techniques. Three different composite mixtures were prepared by varying brass concentrations 1.5, 2.0 and 2.5 wt-% using the glycerin as a plasticizer. The prepared brake pad materials were subjected to density, hardness, thermal stability, friction and specific wear rate analysis. Tribological properties of friction specimen were studied on pin-on-disc type friction testing machine model MMW-1 using nominal contact pressure 7.69 MPa, sliding velocity 1.74 m/s and 1.57 km sliding distance conditions. Microstructural characterization of worn surfaces was carried out using scanning electron microscopy. Obtained test results indicate that brass chips have an important effect on improving tribo-performance. Physical–mechanical characterization of friction composites showed that the use of glycerin improves the physical properties of materials by improving the powder compressibility and reducing the structural defects formed by brass chips. GRAPHICAL ABSTRACT: UF0001